Social inclusion and wellbeing of families of children with special needs transnational study report - Colomeischi, Adina (2018)
BUILDING BRIDGES: PROMOTING SOCIAL INCLUSION AND WELLBEING FOR FAMILIES OF CHILDREN WITH SPECIAL NEEDS – PSI-WELL The project entitled Building Bridges: Promoting Social Inclusion and Wellbeing for Families of Children with Special Needs (PSI_WELL) proposes an innovative approach aimed to facilitate social inclusion and wellbeing for families confronting with disabled children through adult education for parents. The project is addressing to the specific needs of families parenting children with special needs (SN) and it is designed to help parents to improve their coping strategies and to enhance their parenting skills in order to foster their social inclusion and wellbeing. The first aim of our project is to assess the wellbeing, stress related factors and couple relationship of parents of children with special needs. The second aim is to enhance personal resources (such as individual coping, emotion regulation), family resources (such as dyadic coping) and social support for parents of a child with special needs through development, implementing and validating a psycho‐educational and social intervention program. The general aim of the project is promoting social inclusion, equity and wellbeing for risk families in Europe through an intervention program for parents of children with special needs. This will be reached through objectives: (1) Diagnose the level of social inclusion, stress and wellbeing of 1500 families parenting children with special needs through a cross‐sectional and cross‐national research; (2) Developing a psychoeducational & social intervention program for fostering wellbeing for families of children with SN; (3) Validating the psychoeducational &social intervention program for risk families through the implementation with 360 parents from European countries of partnership; (4) Raising the awareness of the communities regarding the specific needs for social inclusion of risk families and disadvantaged parents of children with special needs through conducting an information campaign; (5) Developing a psychoeducational kit comprising two working tools for trainers specialized in working with disadvantaged parents by the end of the project; (6) Improving parenting skills and parent‐child relationships through developing na integrative handbook for parents by the end of the project. The target group comprises 360 parents from six European countries who will be involved in training activities and social network in order to enhance their personal and parental skills for a better social inclusion. The activities describe specific interventions such as a crossnational research on social inclusion, stress and wellbeing of families of children with SN to diagnose the level of stress and wellbeing of parents and the implications for adult education; designing and validating of a Psycho‐Educational & Social Intervention (PESI) Program for enhancing social inclusion and wellbeing of families of children with special needs; developing specific and comprehensive tools to sustain the intervention program (such as: a handbook for parents of children with special needs; a psycho‐educational kit for social‐emotional learning training for parents of children with SN, comprising the trainer’s manual and the trainee’s workbook), developing and implementing a training course for trainers; delivering the training program for parents; creating a network of support groups for parents of children with special needs in order to facilitate knowledge and experiences sharing, fostering social inclusion as well; dissemination of project’s activities and results; sharing the project’s deliverables through website, workshops, symposium, conferences. The expected impact on target groups is twofold: on the one hand is expected a personal development process and on the other hand is expected acquiring specific parenting skills (the results will consist in 360 parents of children with SN more resilient and enabled to practice different parenting strategies in order to respond exactly to their children growing and development needs; they will overcome the social exclusion becoming active involved in the process of raising and supporting their own children with SN). The project expect a community more inclusive and sensitive to the specific needs of families with children with SN and the university will be recognized as an importante resource for quality knowledge and experience (provider of an evidence‐based program). At the national and international level is expected raising the awareness of the political deciders regarding the specific needs of families of persons with SN. The research conducted within the project draws some implications for family’s life within social environment and it will propose some solutions for intervention to enhance the life quality of these families and their social inclusion, so that the results of the Project could serve as a base for developing an educational policy for parents and families of children with SN. Strategic partnership KA2 Stefan cel Mare University of Suceava, Romania ‐ coordinator Lleida University, Spain Politechnik Institute Braganca, Portugal Zagreb University, Faculty of Education and Rehabilitation Sciences, Croatia Klaipeda University, Lithuania Bogazici University, Turkey